Association between Genetic Instability and Helicobacter pylori Infection in Gastric Epithelial Dysplasia. (30th December 2012) - Kim, Jin Su; Chung, Woo Chul; Lee, Kang-Moon; Paik, Chang Nyol; Lee, Kyeong Soo; Kim, Hye Ji; Kim, Young Wook; Jung, Ji Han; Noh, Seung June; Lee, Yun Kyung
Abstract : Background . In gastric carcinogenesis, changes of DNA methylation appear to be an early molecular event, and the genome-wide methylation state is closely correlated with the level of long interspersed nucleotide element-1 (LINE-1) methylation. In this study, we measured LINE-1 methylation level according to genetic instability and evaluated the effect of Helicobacter pylori infection on genetic instability in gastric epithelial dysplasia. Methods . Total 100 tissue samples of gastric epithelial dysplasia were analyzed. Seven loci that linked to tumor suppressor genes were used to identify significant structural chromosomal aberrations. Microsatellite status was investigated for two different microsatellite marker loci (BAT25 and BAT26). Also, we measured LINE-1 methylation level by combined bisulfite restriction analysis (COBRA-LINE-1) method. Results . There were no significant differences of LINE-1 methylation level according to chromosomal/microsatellite instability and H. pylori state. In the dysplastic lesions with H. pylori infection, LINE-1 methylation level of MSI lesion was significantly lower than that of microsatellite stable (MSS) lesion (40.23 ± 4.47 versus 43.90 ± 4.81 %, P < 0.01 ). Conclusions . In gastric epithelial dysplasia with H. pylori infection, MSI is correlated with reduced LINE-1 methylation level. Coexistence of H. pylori infection and MSI might be a driving force of gastric carcinogenesis.